Clinical significance of CD155 expression and correlation with cellular components of tumor microenvironment in gastric adenocarcinoma - Liu, Xue; Xu, Chenyang; Guo, Tianwei; Zhan, Shenghua; Quan, Qiuying; Li, Mengsi; Wang, Ziyi; Zhang, Xueguang; Guo, Lingchuan; Cao, Lei (Frontiers in Immunology, 2023)
CD155 is recently emerging as a promising target in malignancies. However, the relationship between CD155 expression and tumor microenvironment (TME) cell infiltration in gastric adenocarcinoma (GAC) has rarely been clarified. We measured CD155 expression in specimens of gastric precancerous disease and GAC by immunohistochemistry. The association of CD155 expression with GAC progression and cells infiltration in TME was evaluated through 268 GAC tissues and public dataset analysis. We showed that the expression of CD155 was positively correlated with the pathological development of gastric precancerous disease (r = 0.521, P < 0.0001). GAC patients with high CD155 expression had a poorer overall survival (P = 0.033). Moreover, CD155 expression correlated with aggressive clinicopathological features including tumor volume, tumor stage, lymph node involvement, and cell proliferation (P <0.05). Remarkably, CD155 expression positively related to the infiltration of CD68+ macrophages in TME (P = 0.011). Meanwhile, the positive correlation was observed between CD155 and CD31 (P = 0.026). In addition, patients with high CD155 expression combined with low CD3, CD4, CD8, IL-17, IFN-γ or CD19 expression as well as those with high CD155 and α-SMA expression showed significantly worse overall survival (P < 0.05). We conclude that CD155 may play a pivotal role in the development of GAC through both immunological and non-immunological mechanisms and be expected to become a novel target of immunotherapy in GAC patients.